(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
تم إجراء البحث في مقر مركز بحوث درعا التابع للهيئة العامة للبحوث العلمية الزراعية خلال الموسم الزراعي 2003/2004 ، وذلك بغرض دراسة التباينات الموجودة بين بعض الطرز الوراثية المستنبطة من البازلاء المزروعة (Pisum sativum L.) للاستفادة منها أثناء إجراء عملية الانتخاب للطرز الوراثية القَيمة للحصول على أصناف جديدة جيدة. كما قدِر أيضاً معامل الارتباط (معامل بيرسون) بين أزواج الصفات الذي يساعد على تسهيل إجراء الانتخاب في الحقل على أساس الصفات المورفولوجية. دلَت النتائج على توافر مدى كبير من التباين في معظم الصفات المدروسة مما يتيح الفرصة لتحسينها حيث وجد أن صفتي غلة القرون الخضراء وعدد القرون على النبات كانت أعلى القيَم بالنسبة لمعامل الاختلاف الكلي (53.5%, 32.3 %) على التوالي مما يشير إلى أن الانتخاب لهاتين الصفتين لن يكون ذا فاعلية في برامج التربية, في حين تفاوتت قيَم معامل التباين لبقيَة الصفات المدروسة. أوضحت الدراسة أن صفة التبكير بالإزهار ترتبط سلبياً مع غلة القرون الخضراء (-0.87) ، ارتفاع النبات (-0.8), عدد القرون على النبات (-0.74), ومع محتوى البذور الخضراء الطازجة من السكريات البسيطة (-0.36) ، وإيجابياً مع عدد البذور في القرن (0.18)، طول القرن (0.42), محتوى البذور الطازجة من المادة الجافة (0.16), ومع وزن الألف بذرة (0.35). ارتبطت غلة القرون الخضراء إيجابياً مع عدد القرون على النبات (0.70) ,ارتفاع النبات (0.96), عدد البذور في القرن (0.24), درجة امتلاء القرن (0.5), ومع نسبة السكريات البسيطة(0.67). بالمقابل ظهرت علاقة ارتباط سلبية مع طول القرن (-0.27), محتوى المادة الجافة (-0.51), ووزن الألف بذرة(0.67) . This investigation was carried out at Daraa Research Center, General Commission for Scientific Agricultural Research, during the growing season 2003/2004. The main purpose of this study was an attempt to find out the association among the important characters of some pea genotypes and their relative magnitude, which is considered very useful to planning breeding programs when the selection is based on one or more characters. The phenotypic correlation coefficient has been estimated, the results showed that there was a wide range of variability in the most of studied traits and this allowed them to improve. The traits which are yield of fresh green pods and the number of pods per plant were the highest values for the total coefficient of variation (53.5 %, 32.3%) respectively. The study revealed that early flowering negatively correlated with the yield of fresh green pods (-0.87), plant height (-0.8), the number of pods per plant (-0.74), and with the content of simple sugar of fresh green seeds (-0.36), and positively correlated with the number of seeds per pod (0.18), the pod length (0.42), the percent of dry material of fresh green seeds (0.16) and with 1000-seed weight (0.35). In addition, the yield of fresh green pods positively correlated with the number of pods per plant (0.70), plant height (0.96), the number of seeds per pod (0.24), pod-filling (0.5), and with the percent of simple sugar (0.67). However, the negative relationship of correlation appeared in pod length (-0.27), the content of dry material (-0.51), and in 1000-seed weight (-0.67) .